SALES FORECASTING INFORMATION SYSTEM USING THE LEAST SQUARE METHOD IN WINDI MEBEL - Charles Jhony Mantho Sianturi; Elsi Ardini; Nita Sari Br Sembiring (Sekolah Tinggi Pariwisata Mataram, 2020)
Windi Mebel is a business engaged in sales that sell goods and services. This home-based business was established a long time ago, but sales do not get maximum results because consumer interest has also begun to diminish due to competitors selling the same product. Therefore, with the increasingly sophisticated technology at this time it can be utilized to use a system that can forecast sales in the next few years so that the calculations generated when sales forecasting are more accurate, effective and efficient. Sales prediction system or sales forecasting can be used to estimate how much demand or demand for consumers and the market for the products produced. The more requests, the increase in sales results is also greater and as expected. To calculate the prediction of sales, a Least Square Method is applied using sales data a few years ago as a benchmark in predicting sales in the next few years. Based on these problems, the authors carry out a problem solving strategy by creating a system that uses the Least Square method to predict how much demand for furniture products the market wants in the future.